Pisciglobus halotolerans gen. nov., sp. nov., isolated from fish sauce - Somboon Tanasupawat; Jaruwan Thongsanit; Chitti Thawai; Keun Chul Lee; Jung-Sook Lee (My University, 2010)
Two strains of Gram-stain-positive, catalase-negative, tetrad-forming cocci, C01 T and C02, were isolated in Thailand from fish sauce. They were facultatively anaerobic, non-motile and non-spore-forming bacteria. These strains produced l -lactic acid from glucose. They grew at pH 5.0–9.0, at 15–40 °C and in the presence of 10 % (w/v) NaCl. The dominant fatty acid was C 18 : 1 ω9 c . The DNA G+C contents of strains C01 T and C02 were 38.6 and 38.7 mol%, respectively. Strain C01 T was related most closely to Desemzia incerta DSM 20581 T , with a 16S rRNA gene sequence similarity of 96.9 %. The strains could be distinguished clearly from D. incerta DSM 20581 T based on cell morphology, physiological and biochemical characteristics and low levels of DNA–DNA relatedness. On the basis of the data presented, strains C01 T and C02 are considered to represent a novel species of a new genus in the Bacillus – Lactobacillus cluster, for which the name Pisciglobus halotolerans gen. nov., sp. nov. is proposed. The type strain of Pisciglobus halotolerans is C01 T ( = KCTC 13150 T = TISTR 1958 T = PCU 316 T ).
Keywords: Strain (injury); Diamino acid; Probiotics and Fermented Foods